2018
DOI: 10.3991/ijet.v13i02.7816
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Flipped Classroom Strategy on the Academic Achievement of Fourth Grade Students in Jordan

Abstract: This study aimed at investigating the effect of flipped classroom strategy on the academic achievement in the subject of science among fourth grade students in Jordan. The study population consists of all fourth grade students in the Directorate of Private Education in Amman area, totaling 2134 students during the second semester of the academic year 2015-2016. The study sample consists of 44 male and female students who were chosen purposely from the study population. The study sample was distributed into two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 2 publications
4
52
2
2
Order By: Relevance
“…However, only females in experimental group had a statistically significant difference in selfefficacy before and after the intervention. It also contradicts with the study by Elian and Hamaidi (2018), which found that there was no significant difference in the means of achievement scores across gender with the intervention of flipped classroom strategy. It is interesting that these two studies are from a similar cultural context namely Iranian, but yielded different findings in that in those cases the FCM did not make a difference on self-efficacy or reveal any significant gender differences.…”
Section: Discussioncontrasting
confidence: 70%
“…However, only females in experimental group had a statistically significant difference in selfefficacy before and after the intervention. It also contradicts with the study by Elian and Hamaidi (2018), which found that there was no significant difference in the means of achievement scores across gender with the intervention of flipped classroom strategy. It is interesting that these two studies are from a similar cultural context namely Iranian, but yielded different findings in that in those cases the FCM did not make a difference on self-efficacy or reveal any significant gender differences.…”
Section: Discussioncontrasting
confidence: 70%
“…When the literature review with regard to the flipped classroom was examined, it was seen that the model increased achievement in a number of fields including mathematics, foreign languages, science, medicine and engineering (Boyraz, 2014;Ceylan, 2015;Sirakaya, 2015;Turan, 2015;Aydin, 2016;Bhagat et al, 2016;Foldnes, 2016;Gonza´lez-Go´mez et al, 2016;Saglam, 2016;AlJaser, 2017;Atwa, Din and Hussin, 2017;Cakir, 2017, Thai et al, 2017Elian and Hamaidi, 2018;Iyitoglu, 2018). On the other hand, the studies indicated the model was not making a significant enhancement (Davies, Dean and Ball, 2013;Findlay and Mombourquette, 2014;Overmyer, 2014;Touchton, 2015;Duffy, 2016;Yavuz, 2016;Dixon, 2017).…”
Section: The Results With Regard To Academic Achievementmentioning
confidence: 99%
“…Because it has been delivered from the beginning of the course, the students are able to learn at their own pace. The flipped help students" self-learning according to their strengths and individual requirements [9]. Therefore, each person studies at home at their own pace and arrives in the classroom to clarify concepts, thus facilitating the work of learning within it.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a student contributes that "helped her analyze ways to allow other people to better understand, which at the same time helped me to learn and helped me in communicative terms." After this, there are clear benefits of this strategy, reflected through the increase in critical thinking, self-learning, communication skills, and cooperation among students [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation